Decompression Sickness Tipe 1 pada Nelayan Tradisional : sebuah Tinjauan Pustaka - Ni Wayan Dewi; Kadek Diah P Sutanegara; Muhammad N Praramdana; Rizqi Al Kasiron; Decky Aditya Zulkarnaen (Department of Pharmacy, Bumigora University, 2023)
Decompression sickness (DCS) is a collection of symptoms caused by the formation of air bubbles in the blood or tissues during or after a decrease in environmental pressure (decompression). In general, the main symptoms of DCS type 1 (pain-only beds) are muscle pain and weakness. So to diagnose Decompression Disease (DCS) type 1, it is based on the symptoms and the history of diving. Type 1 decompression sickness is managed by choosing initial treatment in the form of giving 100% oxygen through a face mask or, if needed, through intubation. While hyperbaric oxygen therapy can be used for definitive therapy if it is available in primary or secondary health care facilities.